The complete human body : the definitive visual guide - Roberts, Alice, 1973- (New York, N.Y. : DK Pub., 2010)
"Understand the human body as never before, from the smallest components of a cell to complex body systems. Explore human anatomy in incredible detail and clarity through virtually life-size 3-D illustrations and scans. Discover how the body works, how it changes from infancy to old age, and what can go wrong and why"--Cover, P. [4].
The integrated body -- Anatomy. Anatomical terminology ; Body systems ; Anatomy atlas -- How the body works. Skin, hair, and nails ; Musculoskeletal system ; Nervous system ; Respiratory system ; Cardiovascular system ; Lymphatic and immune system ; Digestive system ; Urinary system ; Reproductive system ; Endocrine system -- Life cycle -- Diseases and disorders.
Includes index.
Outstanding Science Trade Books for Students K-12, 2011.
System requirements for accompanying disc: PC Windows XP with service pack 2 or Windows Vista, Intel or AMD processor; soundcard; 24-bit color display; screen resolution 1.024 x 768. Macintosh OS X v10.4; G4, G5, or Intel processor; soundcard; 24-bit color display; screen resolution 1.024 x 768.
Keywords: Anatomy -- Pictorial Works; Physiological Phenomena -- Pictorial Works; Human body -- Pictorial works; Human anatomy -- Pictorial works; Human physiology -- Pictorial works